THE IMPORTANCE OF THE GREAT SILK ROAD IN THE DEVELOPMENT OF CENTRAL ASIAN CIVILIZATION - Zafar Zaripovich, Artikov (PT. Antis International Publisher, 2025)
Objective: This study aims to comprehensively analyze the multifaceted impact of the Great Silk Road on the civilizational development of Central Asia, focusing on its influence on urbanization, intercultural exchange, technological progress, and intellectual life. Method: An interdisciplinary literature analysis was employed, drawing from historical, cultural, and economic sources to synthesize diverse scholarly perspectives on the Silk Road’s role in shaping the region. Results: The research reveals that the Silk Road significantly contributed to the growth of urban centers such as Samarkand and Bukhara, facilitated the spread of religious and philosophical thought, stimulated scientific and literary advancements, and supported the emergence of influential political entities. Novelty: This study offers an integrative framework for understanding the Silk Road as a catalyst of historical globalization in Central Asia, moving beyond conventional trade-focused narratives to highlight its enduring contributions to regional identity and global history. The findings also provide relevant insights for contemporary cultural and economic initiatives that seek to revive the integrative spirit of the Silk Road in modern Central Asia.